Kolaborasi Masyarakat Dalam Program Berbasis Masjid Membangun Desa Padang Ulak Tandung - Juswandi, feby; Calvin Chang; Syifa Zahara; Izzati Ramadhani Herry; Naintyn Novitasari; Zulfadillah Anugrah; Trio Adetia; Yuliana Dwi Puspita Sari; Naza Ardelia Putri; Zakiya Zahratun Nisa; Sakinah Mawahdah (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This study addresses the key issues of environmental cleanliness and community participation in Desa Padang Ulak Tanjung. The main objective is to foster collaboration between students and the community through mosque-based activities to enhance social awareness and collective responsibility. The program includes various initiatives, such as Islamic New Year celebrations, construction of village gates, communal clean-ups, and educational support for children. The research employs a participatory approach, involving direct collaboration with the local community. Data collection methods include observations, interviews, and visual documentation, which are analyzed descriptively. The results demonstrate a significant increase in environmental awareness and active participation in social activities among the villagers. The findings suggest that mosque-based collaboration between students and the community is an effective strategy for addressing local issues and promoting sustainable development in rural areas.